Rodinný dům - Grman, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2017)
V předkládané projektové dokumentaci je zpracován návrh rodinného domu s provozovnou – kancelář. Novostavba rodinného domu je situována v obci Martinice. Zastavěná plocha RD je 200,4 m2. Rodinný dům je navržen pro bydlení čtyřčlenné rodiny. V rodinném domě je navržena také provozovna, kterou bude využívat investor. Rodinný dům má dvě nadzemní podlaží a je částečně podsklepený. Stavba je založena na základových pasech z prostého betonu. Celá stavba je navržena ze systému Porotherm, kromě obvodového zdiva suterénu. Střecha nad 1.NP je řešena jako vegetační plochá s klasickým uspořádáním vrstev pro vegetační střechy. Střecha nad 2.NP je řešena jako nepochůzná plochá jednoplášťová střecha s klasickým uspořádáním vrstev. Bakalářská práce obsahuje studii RD, situační výkresy, stavební dokumentaci, požárně bezpečnostní řešení stavby, stavební fyziku a seminární práci.

In the submitted project documentation is elaborated a design of a family house with an office. The new family house is situated in the village Martinice. The built-up area of the family house is 200,4 square meters. The new house is designed for a family of four. The project documentation also includes the lay-out of the office that will be used by the investor. The family house has two floors and the cellarage under part of the building. The building is based on plain concrete strips. The whole building structure is designed from the Porotherm system, except for the perimeter masonry of the basement. The roof above the first floor is flat and is designed as a vegetative roof with a classic arrangement of layers for vegetative roofs. The roof above the second floor is designed as an impassable flat roof with a conventional single-layer arrangement. This bachelor thesis includes a study of the family house, layout drawings, building documentation, fire safety scheme, building physics and seminar work.
Family house
Keywords: Bakalářská práce; rodinný dům; novostavba; plochá střecha; provozovna.; Bachelor thesis; family house; new building; flat roof; office.